2012
DOI: 10.1063/1.4733333
|View full text |Cite
|
Sign up to set email alerts
|

Affinity and its derivatives in the glass transition process

Abstract: The thermodynamic treatment of the glass transition remains an issue of intense debate. When associated with the formalism of non-equilibrium thermodynamics, the lattice-hole theory of liquids can provide new insight in this direction, as has been shown by Schmelzer and Gutzow [J. Chem. Phys. 125, 184511 (2006) (2011)]. Here, we employ a similar approach. We include pressure as an additional variable, in order to account for the freezing-in of structural degrees of freedom upon pressure increase. Second, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 43 publications
(68 reference statements)
1
19
0
Order By: Relevance
“…They are traditionally formed via a high temperature route, i.e., by freezing-in of a supercooled melt [1,2]. Crystalline zeolites with molecular or nanoscopic porosity, on the other hand, can transform into a low-entropy and low-density amorphous (LDA) phase when exposed to either high pressures or high temperatures [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…They are traditionally formed via a high temperature route, i.e., by freezing-in of a supercooled melt [1,2]. Crystalline zeolites with molecular or nanoscopic porosity, on the other hand, can transform into a low-entropy and low-density amorphous (LDA) phase when exposed to either high pressures or high temperatures [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The requested number of internal variables is classically discussed in relation to the Defay-Prigogine ratio [4], [5], [6], [7], [2], [8], [9]. Without being exhaustive, it is worth mentioning the single structural order parameter approaches of Schmelzer, Gutzow, Tropin and coworkers [10], [11], [12], [13], [14], [15], [8] and the one of Garden, Guillou, Richard and Wondraczek [9], [16]. In the following, these two approaches will be referred to by the acronyms SGT and GGRW respectively.…”
Section: Introductionmentioning
confidence: 99%
“…As a complementary tool to reference [3], we propose an extended thermodynamic analysis of the same model. When trying to apply it to a real liquid/glass, such as in [16] for the extensively studied orthoterphenyl, this in-depth analysis can bring new insight on the physical signification of the model and the choice of the best parametrization methodology.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, Garden et al 10 demonstrated recently that the two affinity-derivative contributions are of fundamental importance in the phenomenological description of the glass transition (see Figs. 5 and 9 in Ref.…”
Section: ∂V ∂ξmentioning
confidence: 99%
“…They are both involved in the thermodynamics describing the temperature and pressure behaviors of the coefficients C p , κ T , and α p and thus in their changes at T g . 10 For non-equilibrium systems (A = 0), it is obvious that the expression (3) above is different from unity. The question now arises whether this departure from unity has something in common with the classical question on measured PD ratios of glasses such as claimed by the authors.…”
Section: ∂V ∂ξmentioning
confidence: 99%